Visualization of protein crystals by high‐energy phase‐contrast X‐ray imaging. Issue 11 (6th November 2019) - Polikarpov, Maxim; Bourenkov, Gleb; Snigireva, Irina; Snigirev, Anatoly; Zimmermann, Sophie; Csanko, Krisztian; Brockhauser, Sandor; Schneider, Thomas R.
Abstract : High‐energy phase‐contrast X‐ray microscopy and tomography of protein crystals in an optically opaque matrix is demonstrated with micrometre resolution on the macromolecular crystallography beamline P14 at PETRA III. Abstract : For the extraction of the best possible X‐ray diffraction data from macromolecular crystals, accurate positioning of the crystals with respect to the X‐ray beam is crucial. In addition, information about the shape and internal defects of crystals allows the optimization of data‐collection strategies. Here, it is demonstrated that the X‐ray beam available on the macromolecular crystallography beamline P14 at the high‐brilliance synchrotron‐radiation source PETRA III at DESY, Hamburg, Germany can be used for high‐energy phase‐contrast microtomography of protein crystals mounted in an optically opaque lipidic cubic phase matrix. Three‐dimensional tomograms have been obtained at X‐ray doses that are substantially smaller and on time scales that are substantially shorter than those used for diffraction‐scanning approaches that display protein crystals at micrometre resolution. Adding a compound refractive lens as an objective to the imaging setup, two‐dimensional imaging at sub‐micrometre resolution has been achieved. All experiments were performed on a standard macromolecular crystallography beamline and are compatible with standard diffraction data‐collection workflows and apparatus. Phase‐contrast X‐ray imaging of macromolecular crystals could find wide application at existing and upcoming low‐emittance synchrotron‐radiation sources.